An interventional study on the stress among adolescents and young adults in Kampung Bahagia Jaya, phase III, Sibu - Abraham Atkin, ak James (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Stress is a non-specific response or reaction of the body to disturbing event in the environment. Stress can cause negative effects to young people. Therefore it is crucial to assess the level of knowledge and awareness among the population so that appropriate interventions can be carried out. The objective of this study was to assess and explore the level of knowledge, perceived level of stress and common coring strategies among adolescents and young adults in Kampung .:Bahagia Jaya Phase III, Sibu from 2ih August 2012 to 4th November 2012. The results obtained were then used as the baseline data to conduct an intervention programme beneficial to the community to enhance their level of knowledge on stress. Data collection was done by using interview-guided questionnaire. Data analysis was done using SPSS software version 20.0. Results showed that 54% of the respondents had good level of knowledge on stress, though less than 50% of them had good knowledge on signs and symptoms and complications of stress. Females (vs males), those at higher (19-35 years old) age group (vs 13-18 years old) and residents who are employed (vs students and those who are unemployed) had significantly higher level of knowledge (p<0.05). Based on the perceived stress scale used in this study, slight higher percentage of respondents has lower level of stress. Among all the coping strategies, religious support was most frequently utilized by the respondents. However, no significant association was found between level of knowledge and family income (p=0.498). No significant association was found between perceived stress level and age group(p=0.92 1), gender(p=0.107), occupation(p=0.206) and family income (p = 0.928). There is no correlation (p>0.05) between level of knowledge on stress and perceived stress level. Post-intervention study showed significant improvement in the level of knowledge on stress (p<0.005). In conclusion, the intervention programme has been effective in increasing the level of knowledge on stress among the respondents, in tenns of general knowledge about stress, stressors, signs arid symptoms, coping strategies and complications of stress.